Did I get this right? Simplifying a fraction

Homework Statement

Simplify: (a2 + 2ab + b2)/(a2 - b2) times (a2 - 2ab + b2)/(a2 - b2)

Homework Equations

(a2 + 2ab + b2)/(a2 - b2) times (a2 - 2ab + b2)/(a2 - b2)

The Attempt at a Solution

Did I simplify this correctly?? (a+b)(a+b)/((a-b)(a+b)) times (a-b)(a-b)/((a-b)(a+b)) = ((a+b)/(a+b)) times ((a-b)/(a-b))
= (a+b)(a-b)/((a+b)(a-b)) = 1 times 1 = 1 Answer

Last edited:

Related Precalculus Mathematics Homework Help News on Phys.org
SammyS
Staff Emeritus
Homework Helper
Gold Member

Homework Statement

Simplify: (a2 + 2ab + b2)/(a2 - b2) times (a2 - 2ab + b2)/(a2 - b2)

Homework Equations

(a2 + 2ab + b2)/(a2 - b2) times (a2 - 2ab + b2)/(a2 - b2)

The Attempt at a Solution

Did I simplify this correctly?? (a+b)(a+b)/((a-b)(a+b)) times (a-b)(a-b)/((a-b)(a+b)) = ((a+b)/(a+b)) times ((a-b)/(a-b)) = (a+b)(a-b)/((a+b)(a-b)) = 1 times 1 = 1 Answer
That's the correct final result. It's hard to say if your steps are correct. You skipped some steps and regrouped things in some rather curious ways.

science_rules